Desain Pembelajaran Kooperatif Tipe Card Sort pada Pelajaran Al-Qur'an Hadits Tingkat Madrasah Tsanawiyah (MTs) - Ida Tresnawati; Indi Milatul Maolah; Iis Khodijah (PT. Pusmedia Group Indonesia, 2023)
The card sort type cooperative learning model in the subject of Al-Qur'an Hadith MTs is in the form of learning by using pieces of paper formed like cards that contain information or subject matter then students group according to the index cards they have. After that students discuss and present the results of discussions about the material from the category of their group. Here the educator acts more as a facilitator and explains the material that needs to be discussed or material that the participants do not understand after the presentation is complete. Research with the title